Myasthenia gravis: diagnostic and management dilemmas. - Palace, J; Vincent, A; Beeson, D (2001)
This review focuses on the diagnostic tests that may help to confirm myasthenia in patients without acetylcholine receptor antibodies, including the newly discovered anti-muscle-specific receptor tyrosine kinase antibody and other investigations. We discuss management dilemmas, particularly those that revolve around treatments whose efficacy is questionable or unproved, such as thymectomy. We review the important issue of how treatments are assessed, and examine future treatment trial designs.